Efektifitas Pengaplikasian Biochar Bambu terhadap Pertumbuhan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Teftae, Oriensi Yakomina Kohe; Noywuli, Nicolaus; Simo, Daniel; Pati, Mikael Lauda (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Shallots are very good for cultivation. The demand for shallots comes from the onion-based industry and household consumption where they are used as cooking ingredients and traditional herbs. With the high market demand for shallots, it becomes an economic opportunity to improve the economy of farmers. One of the problems of shallot cultivation is the low quality of the soil in the form of soil properties such as physical properties, biological properties and chemical properties of the soil and decreasing soil fertility. One effort to improve soil properties and increase soil fertility is by adding soil conditioners in the form of biochar. The purpose of writing this journal is to review the results of previous research in identifying the effect of bamboo biochar application on the growth of shallots. The method used is the library research method. The application of biochar has an effect on the growth of shallot plant yields, in addition the application of biochar can increase the microbial population in the soil.